Faktor Resiliensi Pasien Amputasi: A Systematic Review - M Ruli Maulana; Tintin Sukartini; Sylvia Dwi Wahyuni (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Introduction: Someone who has a physical disability will certainly affect mental health. Therefore we need the ability to be able to adapt so that it can restore the quality of life. Objective: To analyze resilience factors in post-amputation patients. Methods: The database used in this study were Scopus, SAGE, and Cambridge and limited to the last 5 years of publication from 2016 to 2020, full-text articles, and in English. The keywords used were "Resilience" AND "Factor AND Amputation". This systematic review used 10 articles that fit the inclusion criteria. Results: From the 10 articles, it was found that there were several resilience factors in post-amputation patients, namely factors psychological factors such as the ability to hold emotions, physical factors, medical factors, coping adaptation factors, cognitive factors of flexibility (ability to solve problems), optimism factors, social support factors, environmental involvement factors in establishing positive relationships with others, love factors and family support, find meaning, goals and planning perspectives for the future, utilizing personal values and self character. High levels of resilience in post-amputation patients can overcome the threat to support the ability of individuals to adapt and develop positivel. Conclusion: there are several factors in increasing the resilience or resilience of patients after amputation so that they can get up quickly from adversity. Suggestion: Resilience can be used to help someone in dealing with and overcoming difficult situations and can be used to maintain and improve their quality of life. Keywords: resilience; factor; amputation ABSTRAK Pendahuluan: Sesorang yang mengalami kecacatan fisik tentu akan membawa pengaruh pada kesehatan mental. Oleh karena itu dibutuhkan kemampuan untuk dapat beradaptasi sehingga mampu mengembalikan kualitas hidup. Tujuan: Untuk menganalisis factor resiliensi pada pasien pasca amputasi. Metode: Database yang digunakan dalam penelitian ini adalah Scopus, SAGE dan Cambridge terbatas untuk publikasi 5 tahun terakhir dari 2016 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “Resilience” AND “Factor AND Amputation”. Systematic review ini menggunakan 10 artikel yang sesuai dengan kriteria inklusi. Hasil: Dari 10 artikel didapatkan hasil bahwa ada beberapa faktor resiliensi pada pasien pasca amputasi yaitu faktor psikologis seperti kemampuan menahan emosi, faktor fisik , faktor medis, faktor adaptasi koping, faktor kognitif fleksibilitas (kemampuan memecahkan masalah), faktor optimisme, faktor dukungan sosial, faktor keterlibatan dilingkungan dalam menjalin hubungan yang positif dengan orang lain, faktor cinta dan dukungan keluarga, menemukan makna, tujuan dan perspektif perencanaan untuk masa depan, memanfaatkan nilai-nilai pribadi dan karakter diri. Tingkat resiliensi yang tinggi pada pasien pasca amputasi dapat mengatasi ancaman dalam rangka menyokong kemampuan individu untuk beradaptasi dan berkembang secara positif. Simpulan: ada beberapa faktor dalam meningkatkan resiliensi atau ketahan pasien pasca amputasi agar dapat segera bangkit dari keterpurukan. Saran: Resiliensi dapat digunakan untuk membantu seseorang dalam menghadapi dan mengatasi situasi sulit serta dapat digunakan untuk mempertahankan serta meningkatkan kualitas hidupnya. Kata kunci: resiliensi; faktor; amputasi